The Provisions of Suspension and Timing in the Gift - a Comparative Jurisprudence Study- - Suleiman , Najib (Islamic Sciences Journal, 2023)
ABSTRACT This research focused on four issues or points from the subject of the gift, which are very important, and few researchers in the jurisprudential arena have focused on it. The first: the issue of defining the gift, as formulating definitions is one of the most difficult things for researchers, and the second: the difference between comment and timing . A precise issue that deserves to be highlighted and focused on, and the third: the comment on the gift and its provisions, and its research needs linguistic ability and jurisprudential accuracy, and it is one of the issues that few researchers have been exposed to, and the fourth: the issue of timing in the gift, and I have considered in the research a scientific formula that is commensurate with the accuracy of This issue, as many authors and researchers have confused between the concepts of timing and lending, and the research ended up distinguishing between the two concepts.